COVID-19 as a traumatic stressor is an indicator of mental health symptomatology. (June 2021) - Sommer, Jordana L.; Mota, Natalie; Reynolds, Kristin; El-Gabalawy, Renée
Highlights: Nearly 3% endorsed a COVID-19-related index trauma. Those with a COVID-19-related index trauma had increased mental health symptoms. They also endorsed closer proximity to COVID-19 (e.g., knowing someone who was tested). Abstract: The mental health impacts of the COVID-19 pandemic are gaining attention. While many are experiencing increased stress due to COVID-19, some perceive the pandemic as traumatic. This preliminary study identified respondents who endorsed a COVID-19-related trauma as their most stressful traumatic experience (i.e., index trauma). We analyzed data from an online Canadian survey (May-July 2020; N =1, 018). Nearly 3% of participants endorsed a COVID-19-related index trauma. These individuals had increased posttraumatic stress, anxiety, and depressive symptoms compared to the remaining sample. Results may inform targeted screening to identify those who may be at greater risk for COVID-19-related mental health sequelae.